New results concerning the environment of the heliosphere, nearby interstellar clouds, and physical processes in the inter–cloud medium. (September 2020) - Linsky, Jeffrey L; Redfield, Seth; Wood, Brian E.
Abstract: We present our new results concerning the interface between the outer heliosphere and the local interstellar medium (LISM). The three dimensional shape of the Local Interstellar Cloud (LIC) based on 62 sightlines to nearby stars shows a region of very low neutral hydrogen density in the direction of the star ε CMa, the brightest source of extreme-UV (EUV) radiation. This "hydrogen hole" with very weak neutral hydrogen absorption by the LIC and Blue clouds results from photoionization by the EUV radiation from ε CMa. The LIC likely surrounds the heliosphere, but in the direction of the hydrogen hole its neutral hydrogen column density is too low to be measured. Upper limits to this column density and the direction of the Sun's motion through space indicate that the Sun will leave the outer edge of the LIC in less than 1, 900 years. The measured difference between the speed and direction of incoming neutral hydrogen atoms (measured by IBEX and Ulysses) and the flow vector of the LIC indicate that the plasma at the edge of the LIC has a different flow vector than the LIC core. The inter-cloud plasma and much of the Local Cavity are inside the Str¨omgren sphere (also called an H II region) surrounding ε CMa. The outer edges of the LIC and other clouds are Str¨omgren shells that are partially ionized by the EUV radiation from ε CMa and white dwarfs. The Local Cavity could be a Str¨omgren sphere plasma photoionized by ε CMa and hot white dwarfs that contains low density ionized gas that is not hot. An interstellar probe should measure magnetic field and plasma properties in the VLISM between the heliopause and 600–700 au from the Sun and then enter what is likely the Str¨omgren shell outer edge of the LIC. When the Sun leaves the LIC, it will either enter the G cloud, a transition region between the LIC and the G cloud, or ionized Str¨omgren sphere plasma.